Is The Electronic Market Really Uncompetitive? The Importance of The Digital Platform Business Model In E-Market’s Monopolization - Radosław SZULC (Communications of International Proceedings, 2025)
Many articles are devoted to proving the uncompetitive behavior of dominant entities in electronic markets. In economic theory, only a competitive market ensures optimal allocation of resources. In the digital market, competitiveness is combined with the network effect leading to above-average income growth in a short period of time, which leads to an increase in market shares and concentration and, in theory, a deterioration in its competitiveness. Little is known about the basic mechanisms (mechanisms) linking market share with the economic results of companies and how they can facilitate the identification of factors of the relationship between market share and company results. The traditional market concentration indicators used do not confirm the deterioration of its competitiveness even in the case of the largest entities of the electronic market. The task of economists is to examine the real threat to the competitiveness of the digital market by using the network effect. Using HHI indicators, the Lerner index and the sales profitability index, the competitiveness of the market was analyzed in terms of potential monopolization. None of the measures used indicate a monopolistic structure or the threat of market monopolization by the sales platform business model. In light of the findings, it seems that the only factual premise that threatens market competition is not the above-average market shares of large digital entities or their revenues and, consequently, possible profits, but the use of unfair business practices and the lack of appropriate supervision by regulatory authorities.
Keywords: competition; network effects; market concentration; market competitiveness